Pendampingan Psikososial Anak Korban Banjir dengan Trauma Healing dan Dukungan Kebutuhan Dasar di Gampong Tanjung Punti - Arief Rahman; Mainisa Mainisa; Muhammad Hatta; Irma Yurni; Ekamaida Ekamaida; Ghazali Syamni (IMPACT: Journal of Community Service, 2026)
Floods that occurred in Gampong Tanjung Punti at the end of 2025 were associated with changes in the psychosocial conditions of children as a vulnerable group. Initial observations revealed that some children appeared anxious, less socially interactive, and still displayed fear-related expressions when recalling the flood event. This situation served as the basis for implementing a community service program integrating trauma healing, basic needs fulfillment, and spiritual support. The program aimed to support psychosocial assistance for flood-affected children through a participatory and child-friendly approach involving 35 children aged 5–12 years, village officials, and local community members. Activities included the distribution of basic supplies and clothing, provision of Qur’an copies, and trauma healing sessions through educational games, drawing, storytelling, and simple relaxation exercises. The results of the activities indicated increased children’s participation, improved emotional expression, and a growing sense of safety during the sessions. In addition, basic needs support and spiritual assistance were perceived to help reduce community burdens in the early post-disaster phase. The holistic approach integrating psychosocial support, basic needs fulfillment, and spiritual dimensions indicates potential support for early recovery processes among flood-affected children and communities.